1992
DOI: 10.1021/bi00124a018
|View full text |Cite
|
Sign up to set email alerts
|

Peptide secondary structure induced by a micellar phospholipidic interface: proton NMR conformational study of a lipopeptide

Abstract: The conformational change of the model peptide Ac-K-G-R-G-D-G-amide induced by a phospholipidic interface was investigated by proton nuclear magnetic resonance (1H NMR). In aqueous solution, the free peptide is highly flexible and disordered, even in the presence of deuterated dodecyl-phosphocholine (DPC-d38) micelles which mimic a membrane interface. The lipopeptide, obtained by grafting a lipid anchor [2,3-dipalmitoyl-D-(+)-glyceric acid] to the lysine side chain of the peptide, was studied by standard 2D 1H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 34 publications
(37 reference statements)
1
21
0
Order By: Relevance
“…[17][18][19] Introduction of disulfide bridges can stabilize folded structures 20 by destabilizing unfolded ones. 32 A Fourier transform infrared reflection absorption spectroscopic study of N-octadecanoyl (Gly) n ethyl ester monolayers and Langmuir-Blodgett films, where n ϭ 1-5, demonstrated that the peptide-amphiphiles could form polyGly II helices while the oligoGly peptides themselves could not. Such noncovalent assemblies have utilized (a) chelators attached to peptides and appropriate metals to initiate interstrand association [21][22][23][24] or (b) lipids covalently attached to peptides that promote association via hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Introduction of disulfide bridges can stabilize folded structures 20 by destabilizing unfolded ones. 32 A Fourier transform infrared reflection absorption spectroscopic study of N-octadecanoyl (Gly) n ethyl ester monolayers and Langmuir-Blodgett films, where n ϭ 1-5, demonstrated that the peptide-amphiphiles could form polyGly II helices while the oligoGly peptides themselves could not. Such noncovalent assemblies have utilized (a) chelators attached to peptides and appropriate metals to initiate interstrand association [21][22][23][24] or (b) lipids covalently attached to peptides that promote association via hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of such an environment is exemplary. In a recent paper (Macquaire et al, 1992b), we showed that a membrane-like interface was able to induce a specific secondary structure in a small peptide anchored within the interface. In the present paper, we report the influence of the same micellar environment on a peptide the size of which is larger than that of lipidic molecules.…”
mentioning
confidence: 96%
“…Moreover, liposomes as lipid carriers have been extensively evaluated as delivery vehicles for drugs, genes and/or cosmetics [12]. Liposomes undergo the problem of both chemical and physical instability; hence, the concept of proliposomes was introduced [13].…”
Section: Liposomes/niosomes and Their Pro-formsmentioning
confidence: 99%